Cardiomyocyte Proliferation from Fetal- to Adult- and from Normal- to Hypertrophy and Failing Hearts - Sanford P. Bishop; Jianyi Zhang; Lei Ye (Biology, 2022)
The cardiomyocyte undergoes dramatic changes in structure, metabolism, and function from the early fetal stage of hyperplastic cell growth, through birth and the conversion to hypertrophic cell growth, continuing to the adult stage and responding to various forms of stress on the myocardium, often leading to myocardial failure. The fetal cell with incompletely formed sarcomeres and other cellular and extracellular components is actively undergoing mitosis, organelle dispersion, and formation of daughter cells. In the first few days of neonatal life, the heart is able to repair fully from injury, but not after conversion to hypertrophic growth. Structural and metabolic changes occur following conversion to hypertrophic growth which forms a barrier to further cardiomyocyte division, though interstitial components continue dividing to keep pace with cardiac growth. Both intra- and extracellular structural changes occur in the stressed myocardium which together with hemodynamic alterations lead to metabolic and functional alterations of myocardial failure. This review probes some of the questions regarding conditions that regulate normal and pathologic growth of the heart.